ANALISIS PESAN DAKWAH PADA PODCAST LOG IN #CLOSETHEDOOR TAHUN 2025 - Nirzam, Eko; Wijayanti, Rani Ika; Rachman, Arief (Holistik: Journal for Islamic Social Sciences, 2024)
The LOGIN podcast, featured on Deddy Corbuzier’s YouTube channel and hosted by Habib Husein Ja’far and Onadio Leonardo (Onad), represents an innovative form of digital da'wah that combines religious discourse with popular culture. Students of the Faculty of Da'wah and Islamic Communication at UIN Siber Syekh Nurjati Cirebon can utilize this podcast as a key subject of study to understand how Islamic messages are delivered in a casual yet meaningful way. This study aims to identify the da'wah messages presented in four selected LOGIN episodes, analyze their modes of delivery, and explore the Islamic values conveyed in each discussion.This research employs a descriptive qualitative method using a hermeneutic approach to interpret the meanings of da'wah messages within the context of digital media. Data were collected through in-depth observations of four selected episodes from 2025, namely those featuring Boris Bokir, Soimah, Fajar Sadboy, and Vior Vincent. Analysis focuses on the content of conversations, specific scene durations, and the inclusion of Qur’anic verses and hadiths in the dialogue.Findings show that the LOGIN podcast delivers messages of faith (aqidah), ethics (akhlak), and Islamic law (sharia) through a lighthearted, humorous, and conversational style. This approach makes da'wah more accessible to young audiences and lay communities. Islamic values such as monotheism, interfaith tolerance, self-reflection, and social ethics are presented through inclusive, open-ended discussions. The podcast's format has proven to be an effective means of spreading Islamic teachings in the digital era and positively influences the audience’s religious understanding.